Contribution of Latvian Technical Intelligentsia to Development of Terminology Until the Establishment of the Republic of Latvia - Māris Baltiņš (History of Engineering Sciences and Institutions of Higher Education)
The article considers the development of technical terminology in the Latvian language until the proclamation of the independent state of Latvia in 1918. The activists of the National Awakening became the first creators of technical terminology, describing current technical innovations as, for example, Juris Alunāns (1832–1864) did in 1860 for the telegraph. The need for technical terms became apparent after the Second Baltic Agricultural Exhibition when difficulties arose in describing the showcased exhibits in Latvian. Significant steps in the development of terminology were made on the initiative of student Mikus Skruzītis (also Skruzīšu Mikus; 1861–1905), who suggested collecting frequently used names of parts of various simple devices, and the initiative of Nikolajs Puriņš (also Puriņu Klāvs; 1858–1935) to publish self-education materials in construction («Būvskola» or Building School) and mechanical engineering («Mašīnu būvskola» or Machine Building School). As the proportion of Latvians employed in the industry and the number of persons who received technical education increased, the need to establish organizations that would take care of both technical education in Latvian and the coinage of the necessary terms became more apparent. The Baltic Technical Society (1906) and the Latvian Educational Society (1908), which established their own terminology committees, deserve special recognition. Encyclopaedic dictionaries were also important for the systematization of terminology, especially the conversational dictionary published by the Knowledge Committee of Riga Latvian Society (1903–1921). The research was carried out within the project «Mūsdienu latviešu valodas lietojums un attīstība» (Research on Modern Latvian Language and Development) of the National Research Program of the Latvian Council of Science (No. VPP-LETONIKA-2022/1-0001).